Stratification of Vunerability Level to coronavirus disease (COVID-19) in particular areas of Family Health Strategy in the city of Crato, Ceará (Research, Society and Development, 2020)
To stratify the level of vulnerability related to the new coronavirus in families of particular areas of two Strategies of Family Health (SFH) and describe preventive interventions performed along with families in more risk. It is about a study descriptive transversal held in Crato, Ceara, Brazil, during the months from april to july 2020. In one of the SFH, 512 families were qualified according to its level of vulnerability, considering that, 74 (14,4%) were high level, 285 (55,7%) medium level and 153 (29,9%) low level. In the second SFH were qualified 253 families being 19 (7,5%) of high level, 149 (58,9%) medium level and 85 (33,6%) low level of vulnerability. The intervention along with more vulnerable families took place through home visits and educational actions, based on the level of vulnerability and aimed at the most vulnerables families. The study of vulnerability related to the new coronavirus in the territory justified the elaboration of preventive interventions of informative purposes.